2016
DOI: 10.1007/s00018-016-2282-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cAMP signaling

Abstract: Cyclic adenosine 3, 5′-monophosphate (cAMP) is a ubiquitous second messenger regulating many biological processes, such as cell migration, differentiation, proliferation and apoptosis. cAMP signaling functions not only on the plasma membrane, but also in the nucleus and in organelles such as mitochondria. Mitochondrial cAMP signaling is an indispensable part of the cytoplasm-mitochondrion crosstalk that maintains mitochondrial homeostasis, regulates mitochondrial dynamics, and modulates cellular stress respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 149 publications
0
72
0
1
Order By: Relevance
“…The G iα subunit can activate ERK1/2 primarily through inhibiting AC and altering Ras-dependent. The inhibited AC activity can decrease the cAMP level and PKA activity (F. Zhang et al, 2016). This process will activate Ras, the upstream molecule of C-Raf (Goldsmith & Dhanasekaran, 2007).…”
Section: Erk1/2 Signaling Pathwaymentioning
confidence: 99%
“…The G iα subunit can activate ERK1/2 primarily through inhibiting AC and altering Ras-dependent. The inhibited AC activity can decrease the cAMP level and PKA activity (F. Zhang et al, 2016). This process will activate Ras, the upstream molecule of C-Raf (Goldsmith & Dhanasekaran, 2007).…”
Section: Erk1/2 Signaling Pathwaymentioning
confidence: 99%
“…Several investigations in last decades of the past century reported that, cyclic adenosine monophosphate (cAMP) plays an important role to influence cell growth, differentiation, proliferation and protein synthesis depending on the source of cells and experimental conditions (Bang et al, 1992; Florin-Christensen et al, 1993; Zhang et al, 2016). Takei et al (1997) found significant increase of protein production in keratinocytes subjected to cyclic strain.…”
Section: Second Messengers System In Strain-induced Responsesmentioning
confidence: 99%
“…Mitochondria are subcellular organelles responsible for oxidative phosphorylation (OXPHOS), producing ~ 80% of the ATP in eukaryotic cells 1 , apoptosis and cell-cycle regulation 2 , redox-and calcium homeostasis 3 as well as intracellular signaling 4 . Each mitochondrion contains 2 -10 copies of a 16.6 kb double-stranded mtDNA containing 37 genes 5 .…”
Section: Introductionmentioning
confidence: 99%